Peregrinos, monarcas e bispos: as peregrinações a Santiago de Compostela no contexto da Reforma Papal (séculos XI e XII) - Foga, César Augusto Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This dissertation deals with pilgrimages to Santiago de Compostela in the context of the socalled Papal Reform (11th - 12th centuries). We argue that the reform of the Roman Church between the middle of the 11th century and the beginning of the 12th century contributed to the ascension of Santiago de Compostela as one of the main pilgrimage centers in Western Christendom. Furthermore, we demonstrate that a closer relationship between the Spanish monarchy and the clergy at the time also contributed to such an outcome. We draw on the Historia Compostelana as our primary historical source. The period considered here (middle 11th century - early 12th century) coincides with Alfonso VI's rule as king of León (1065-1109) and Diego Gelmirez (1100-1140) as bishop and eventually archbishop of Compostela. It was Alfonso VI and Diego Gelmirez, together with reformist popes, who made Compostela the main pilgrimage center in Western Christendom in the 12th century

A presente dissertação trata sobre as peregrinações a Santiago de Compostela no contexto da chamada Reforma Papal (séculos XI e XII). O objetivo é evidenciar que o programa de reformas instituído pela Igreja de Roma entre meados do século XI e início do XII contribuiu para a ascensão de Santiago de Compostela como um dos principais centros de peregrinação da Cristandade. Ademais, demonstraremos que a aproximação entre as monarquias cristãs da Hispânia e o clero na referida época também auxiliou em tal feito. Utilizamos como fonte de pesquisa a Historia Compostelana, o período histórico abordado pela obra compreende o final do século XI e início do XII, momento esse que coincide com o reinado de Alfonso VI de Leão (1065-1109) e do bispo e, posteriormente arcebispo da igreja de Compostela, Diego Gelmirez (1100-1140), personagens esses que com o auxílio dos papas reformadores fizeram de Compostela o principal centro de peregrinação da Cristandade no século XII
Keywords: Igreja Católica História Espanha; Papas; Santiago de Compostela (Espanha); Santiago de Compostela (Spain)